Development Of Employment Of Zakat And Waqf For Remote Communities: The Case Of The Al-Qur'an Waqf Board - Tiswarni, Tiswarni; Jalal, Afifah; Hadi, Sutrisno (Universitas Islam Negeri Raden Fatah Palembang, 2023)
This paper discusses the development of utilization of zakat and waqf funds managed by the Al-Qur'an Waqf Agency (BWA) in order to help the community, especially on remote islands and remote areas during a pandemic. The purpose of this paper was to get an overview of the development of forms of utilization of zakat and waqf funds by BWA in helping the community. This paper belonged to the field of research on Islamic law and social institutions with a qualitative type of research. Data was collected through interviews and documentation, and analyzed using descriptive analysis. The results of the study stated that BWA developed forms of utilization of zakat and waqf in the health, religious and socio-economic sectors, by creating the Against Covid-19 Strengthen Indonesia program. The old programs were still a priority, such as several waqf programs and Peer to Peer Zakat. The conclusion of this paper was that the development carried out by BWA in utilizing zakat and waqf was carried out by analyzing the current pandemic situation. They remain focused on the old program while opening humanitarian services for people affected by Covid-19 on remote and inland islands.